Identification of Risk Factors for Urinary Tract Stones in Rural Populations : A Systematic Review - Vachroul Rauzi; Dinda Pebriani Simbolon; Heri Setiawan; Yuni Agnes Lubis; Nasribar (The International Journal of Medical Science and Health Research, 2026)
Introduction: Urinary tract stones (UTS) are a growing global health concern, yet risk factors in rural populations remain poorly synthesized due to distinct environmental, occupational, and dietary exposures. This systematic review identifies significant risk factors for UTS specifically in rural settings. Methods: A systematic review of 80 studies (RCT, etc) from global databases was conducted. Studies were included if they reported on rural populations or provided separate rural subgroup analyses for UTS risk factors. Results: Key positive risk factors identified include: male sex (male-to-female ratio up to 10.5:1 in endemic pediatric bladder stone disease) (2,3); family history (OR=16.98, 95%CI:3.02-95.25) (9); low fluid intake (OR=2.64, 95%CI:2.00-3.48) (6); red meat consumption (OR=32.28, 95%CI:9.7-143.2) (9); high sodium (OR=1.88) (6); obesity (OR=2.36) (6); diabetes (OR=1.68) (4); hypertension (OR=2.04) (4); ambient temperature (10% increased risk per 5°C) (7); occupational heat exposure (ninefold risk) (8); cadmium exposure (RR=1.07 per 1.0 µg/L urinary cadmium) (12); and phthalate exposure (13). Hypocitraturia (91.3% prevalence) and hypercalciuria (68.5%) were the most common metabolic abnormalities in rural stone formers (5). Distinct rural stone types include ammonium urate (endemic bladder stones in South Asian children) (2) and struvite (infection-related). Discussion: Rural UTS risk operates via three distinct pathways: 1) poverty-driven endemic disease (protein deficiency, dehydration, infection) producing ammonium urate stones; 2) adult calcium oxalate disease driven by nutritional transition (metabolic syndrome, high animal protein, low fluid intake); and 3) environmental toxicant-related disease (cadmium, phthalates) from agricultural/industrial exposures. Healthcare access barriers delay diagnosis, increasing stone burden at presentation (14). Conclusion: Rural populations face unique, amplified UTS risk factors requiring context-specific interventions: ensuring potable water access at worksites, dietary protein supplementation in endemic bladder stone regions, metabolic syndrome management, and environmental remediation of heavy metals.